2012
DOI: 10.1038/jcbfm.2012.184
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Diffusion and T2: MRI Predictors of Acute Mountain Sickness during Sustained High-Altitude Hypoxia

Abstract: Diffusion magnetic resonance imaging (MRI) provides a sensitive indicator of cerebral hypoxia. We investigated if apparent diffusion coefficient (ADC) and transverse relaxation (T 2 ) predict symptoms of acute mountain sickness (AMS), or merely indicate the AMS phenotype irrespective of symptoms. Fourteen normal subjects were studied in two groups; unambiguous AMS and no-AMS at 3,800 m altitude (intermediate AMS scores were excluded). T 2 relaxation was estimated from a T 2 index of T 2 -weighted signal normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 27 publications
8
26
0
Order By: Relevance
“…Although contradictory to the conventional hypothesis, our findings of focally reduced brain water during acute normobaric hypoxia do agree with the recent findings of reduced T 2 -weighted signal intensity during prolonged residence (7 days) at terrestrial altitude. 8 Using a combination of TBSS and ROI analyses, we identified that 2 hours in hypoxia caused a focal reduction in mean diffusivity within the posterior left hemisphere (TBSS) that propagated throughout cerebral white matter by 10 hours (using both TBSS and skeletonized regions of interest). After both 2 and 10 hours in hypoxia, concomitant increases in fractional anisotropy were also observed using a region of interest analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although contradictory to the conventional hypothesis, our findings of focally reduced brain water during acute normobaric hypoxia do agree with the recent findings of reduced T 2 -weighted signal intensity during prolonged residence (7 days) at terrestrial altitude. 8 Using a combination of TBSS and ROI analyses, we identified that 2 hours in hypoxia caused a focal reduction in mean diffusivity within the posterior left hemisphere (TBSS) that propagated throughout cerebral white matter by 10 hours (using both TBSS and skeletonized regions of interest). After both 2 and 10 hours in hypoxia, concomitant increases in fractional anisotropy were also observed using a region of interest analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, we explored the relationship between the development of a specific acute mountain sickness symptom, headache, with changes in brain water mobility and content after 2 hours (presymptomatic) and 10 hours (symptomatic) in hypoxia. Given the lack of molecular evidence for breakdown of the bloodbrain barrier in hypoxia, 10,11 but evidence for the accumulation of both extracellular and intracellular water, 3,4,8 we hypothesized that early hypoxia (2 hours) will be characterized by a reduction in mean diffusivity and increased fractional anisotropy but no change in T 2 in line with a fluid shift into the intracellular space. In contrast, more prolonged hypoxia (10 hours) will be associated with reduced mean diffusivity but increased fractional anisotropy and T 2 , which would suggest an increase in brain edema.…”
Section: Introductionmentioning
confidence: 99%
“…2012, 2013; Hunt et al. 2013). Furthermore, increases in FA values in the corticospinal tract and CC were only found in HA immigrant descendants (Zhang et al.…”
Section: Introductionmentioning
confidence: 99%
“…A reduction in ADC is generally Hypoxia, exercise, and cerebral volume T Rupp et al interpreted as a consequence of cytotoxic edema with intracellular swelling and may be associated with perturbations in cellular energy status responsible for reduced Na + /K + ATPase pump and altered ionic homeostasis. 9,25 Previous studies regarding the effect of hypoxic exposure on ADC reported contradictory results with increased 3,4,14 or reduced 5,10 ADC values. Hunt et al 9 reported significant reduction in ADC values among subjects with AMS after 48 hours at 3,800 m while ADC was increased in subjects without AMS.…”
Section: Correlationsmentioning
confidence: 99%
“…The absence of correlation between symptoms of AMS and changes in brain volume or ADC during 10 hours of hypoxic exposure cannot exclude any consequences of cerebral changes over longer hypoxic exposure duration where symptoms are known to be the most severe (12 to 48 hours). 9 …”
Section: Study Limitationsmentioning
confidence: 99%